Giant Granular Cell Tumor of the Left Thigh, a Rare Case Report and Literature Review - Liu Q; Kong X; Yang J; Zhang D (Orthopedic Research and Reviews)
Qian Liu,1,* Xiangyu Kong,2,* Jun Yang,3 Dongdong Zhang1 1Department of Oncology, Xiangyang No. 1 People’s Hospital, Hubei University of Medicine, Xiangyang, 441000, People’s Republic of China; 2Department of Radiology, Xiangyang No. 1 People’s Hospital, Hubei University of Medicine, Xiangyang, 441000, People’s Republic of China; 3Department of Neurology, Xiangyang No. 1 People’s Hospital, Hubei University of Medicine, Xiangyang, 441000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Yang, Department of Neurology, Xiangyang No. 1 People’s Hospital, Hubei University of Medicine, Xiangyang, 441000, People’s Republic of China, Email 296051103@qq.com Dongdong Zhang, Department of Oncology, Xiangyang No. 1 People’s Hospital, Hubei University of Medicine, Jiefang Road No. 15, Xiangyang, Hubei, 441000, People’s Republic of China, Tel +8615072278600, Email zhangdongdong@whu.edu.cnBackground: Granular cell tumor (GCT) is a rare soft tissue tumor characterized by Schwann cell differentiation. While GCT can occur in any part of the body, it is less common in the lower limbs. We report a case of a giant atypical GCT located in the left thigh, the tumor was initially small and painless at the time of discovery but gradually grew to 17 cm over a two-year period.Case Presentation: A 60-year-old male patient presented to our hospital two years ago with a painless mass measuring 39× 22 mm on the left thigh. He refused treatment due to the absence of discomfort. Over the following two years, the painless mass gradually enlarged. Magnetic resonance imaging (MRI) upon admission revealed a mixed signal, spindle-shaped shadow measuring approximately 170 mm × 50 mm × 55 mm in the left femur’s subcutaneous soft tissue, accompanied by mild surrounding swelling. Surgical resection was performed. Microscopic examination revealed round or polygonal tumor cells distributed in sheets or nests, with no evident atypical cells or signs of nuclear division. Immunohistochemistry demonstrated positive staining for S100, SOX-10, Vimentin, NSE, CD56, and H3K27Me3 in the tumor cells, with a Ki-67 labeling index of approximately 15%. The postoperative pathological diagnosis confirmed giant GCT.Conclusion: We report a case of a benign giant GCT in the left thigh. Early diagnosis and treatment of painless lower-limb masses are essential to prevent their enlargement or malignant transformation. Surgery remains the primary treatment for this condition. Pathological assessment is crucial for definitive diagnosis and for distinguishing between benign and malignant forms.Keywords: granular cell tumor (GCT), lower limb, soft tissue tumor, histopathology, surgery